Nagorno-Karabakh and Conflict Resolution in the Realist Tradition of IR - Ditrych, Ondřej (Czech Journal of International Relations, 2006)
This study argues that due to a lack of attention paid to the national interest of actors in international politics the mainstream international conflict resolution studies fail in their prescriptive and descriptive aspects; particularly when conflicts are complicated by geopolitics. The case study of the long-standing conflict in Nagorno-Karabakh is used to highlight the strengths of geopolitical analysis, aimed at a proper understanding of a conflict’s causes and the identities and interests of the actors directly and indirectly involved. This understanding is a prerequisite for coordinated international action directed towards the creation of the structural conditions for peace which would lead the prime actors of the conflict to choose peaceful resolution as a means to escape the hurting stalemate situation. In the case of Nagorno-Karabakh - a conflict whose resolution has been impeded mainly by Azerbaijani and Armenian ethnic nationalism, coupled with fierce competition between the major powers in Central Eurasia - a geopolitical analysis leads to the conclusion that the key to the resolution of the conflict lies in the hands of Russia. Such a resolution therefore presupposes a redefinition of Russia’s interests, which would be based on the rational calculation that a deliberate destabilization of the South Caucasus will, in long term, hurt her interests.